MODEL OF TRANSFORMATIONAL LEADERSHIP IN CAMPUS BASED ON SALAF ISLAMIC BOARDING SCHOOL - Sarkowi, Sarkowi (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
Standing and developing in the environment of the Miftahul Ulum Lumajang Islamic boarding school which still maintains its salafism based on teachings in the Islamic Salaf book Ahlu Sunnah Wal Jamaah An-Nahdliyah demands a leadership model that transforms the vision, mission and values of the pesantren into a source of energy in realizing campus vision and motivating the entire academic community of Miftahul Ulum Lumajang Islamic College (STAIM). This study aims to describe and analyze transformational leadership on a campus based on a salaf Islamic boarding school. This type of research is qualitative research with a case study approach to reality which is collected using various techniques of in-depth interviews, participatory observation, and documentation. The results showed that the transformational leadership model applied was the transformational leadership model at Miftahul Ulum Lumajang Islamic High School based on and integrated with the values and culture of the Miftahul Ulum Islamic Boarding School Banyuputih Kidul Kidul Lumajang and has been able to effectively and efficiently improve the strengthening and development of institutions STAIM Lumajang campus.